FORMULASI SEDIAAN GEL ANTIBAKTERI EKSTRAK ETANOL 70% DAUN BINTARO(Cerbera odollam Gaertn.) TERHADAP Staphylococcus aureus - Ferry Effendi; Herson Cahaya Himawan; Firdhan Ausia Syahidin (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2018)
Ethanol extract 70% of bintaro leaves could inhibit the growth of Staphylococcus aureus bacteria. Bintaro leaf extract (Cerbera odollam Gaertn) has chemical content of flavonoids, alkaloids and tannins. In this research was made preparation gel ethanol extract 70% from bintaro leaves (Cerbera odollam Gaertn.) and determine the formulation of gel preparation having good physical quality and have antibacterial effectivity. Physical quality tested such as homogeneity, organoleptic, viscosity, pH, spreadability, stability and antibacterial effectiveness test against Staphylococcus aureus bacteria using the disk diffusion method. The results showed that ethanol extract gel of 70% of bintaro leaves had good physical quality and best antibacterial effectiveness was found in Formulation III with 5% concentration. Based on one-way ANOVA analysis with Duncan assay, each formulation with different concentrations had a significant difference with α = 0.05.